Essential NMR For Scientists and Engineers - Blümich, Bernhard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The second edition of this textbook offers extended information on imaging as well as relaxation. A new chapter has been added to cover hyperpolarisation. As before, Essential NMR is a set of lecture notes for scientists and engineers who want to brush up on their knowledge of NMR. It is also a compendium for graduate and postgraduate students of physics and chemistry as well as for their teachers, covering all fields of NMR, i.e. NMR methodology and hardware, chemical analysis, 2D-spectroscopy, NMR imaging, flow NMR, and quality control NMR. The material, selected and organized for a one-semester course, is presented in a concise and informative way. Each page addresses a particular topic and holds an illustrative figure as well as explanatory text providing the key information. The book is intended for beginning graduate students and doctoral students of Physics, Chemistry, Chemical Engineering, and Material Science.
Introduction -- Basic Principles -- Spectroscopy -- Imaging and Transport -- Relaxometry and Laplace NMR -- Hyperpolarization.
Keywords: Analytical chemistry; Spectrum analysis; Materials -- Analysis; Biology -- Technique; Condensed matter; Polymers; Analytical Chemistry; Spectroscopy; Characterization and Analytical Technique; Biological Techniques; Condensed Matter Physics; Polymers